Formation of Eurasian identity through the discourse of the President's messages to the people of Kazakhstan - Seilkhan, B.; Ding, F.; Taishanova, S.T. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Kazakhstan, as a trans-regional, multi-ethnic state located between Asia and Europe, faced unique challenges and opportunities during the process of forming its identity as an independent nation-state following the events of 1991. The objective of this article is to examine the President's messages to Kazakhs from 1997 to 2023 and pinpoint the frequency of mentions of Eurasianism concepts. Studying the President's Address to the People allows us to understand the features and the evolution of Eurasian identity in Kazakhstan. The study's results demonstrate that the emphasis on Eurasian identity in Kazakhstan has changed over time and in the international political context under the influence of internal and external political, economic and cultural factors. In the 1990s, the Presidential Messages to the People discussed the Eurasian identity of Kazakhstan in terms of its geographical location and historical affiliation. However, in the 21st century the country began to actively promote the integration of the Eurasian region together with Russia. But with the development of Kazakhstan itself and the hegemonic manifestations of Russia, Eurasian integration ceased to be a priority for the state, especially during the presidency of K. Tokayev, and relative importance began to be attached to the special position of Kazakhstan in the Eurasian region. A limitation of this study is that using only the State of the Union Address for analysis may not fully reflect the factors shaping the Eurasian identity. Future studies may include other data sources and methodologies to provide a more complete picture.